Desmoid Tumors: A Review of the Literature and Pharmacologic Management. (2nd April 2016) - Sivanesan, Eellan; Gitlin, Melvin C.
ABSTRACT: Desmoid tumors represent a nonmalignant proliferation of fibroblast-related cells. These rare tumors are difficult to treat and often persist as indolent, lifelong conditions. There are a number of treatments available for both anatomic and symptom regression. Some of these treatments, unfortunately, may not provide long-lasting results and may result in further complications. Pain is a distressing symptom that may be due to the tumor itself or the result of utilized treatments. Pharmacologic therapies represent a noninvasive alternative to surgical resection. Pain symptoms require therapeutic regimens that must be modified as the tumor evolves in expression. The individualized pain treatment program utilized may often reflect principles used in both nonmalignant and malignant pain management models. This review seeks to increase awareness of desmoid tumors through a review of the literature and discussion of its pharmacotherapeutic management.